Efectividad del programa educativo niños saludables en el conocimiento sobre nutrición en escolares-Pacasmayo - Carrillo Urteaga, Miluska Maribel (2016)
This research study, quantitative experimental and pre kind was held in the Educational Institution No. 80407 Ugas Gonzalo Salcedo in the province of Pacasmayo, in order to determine the level of knowledge about nutrition in school. The sample consisted of 30 students who met the inclusion criteria. A questionnaire was used to determine the level of knowledge of school nutrition, for data collection information being obtained, processed and analyzed statistically; the results are presented in tables of double entry. After the analysis has led to the following conclusions: before the implementation of the educational program, 50 percent of schoolchildren presented a medium level of knowledge, 33.3 percent reached a low level of knowledge, and a 16.7 percent level high knowledge; after application of the educational program, 83.3 percent of school I reach a higher level of knowledge and 16.7 percent had an average level of knowledge. The educational program was effective in improving the level of knowledge about nutrition of schoolchildren in more than 25 percent (p < 0.05). Key words: Educational program, Knowledge about nutrition, school